2022
DOI: 10.1002/elsc.202200002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SDS‐coated iron nanostructure on the gene expression of bio surfactant‐producing genes by Pseudomonas aeruginosa

Abstract: Bio surfactants are natural surfactants that induce emulsification, displacement, increased solubility, and mobility of hydrophobic organic compounds. In this study, the gene expression of biosurfactant production genes by Pseudomonas aeruginosa in the presence of sodium dodecyl sulfate coated iron nanostructure (Fe/SDS) were evaluated. Emulsification Index and Surface Tension reduction test to check stability and emulsification the rhamnolipid were done. Purification was evaluated using thin layer chromatogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The bacterial genera Pseudomonas and Bacillus are the ones that are utilized the most frequently in biosurfactant manufacturing. A significant number of currently available publications have demonstrated their efficacy in biosurfactant production and their role in successfully managing phytopathogens [5,117–119] . Varnier et al., [120] concluded that Pseudomonas aeruginosa produced Rhamnolipid biosurfactants that improved grapevine immunity against Botrytis cinerea .…”
Section: Application Of Biosurfactantmentioning
confidence: 99%
“…The bacterial genera Pseudomonas and Bacillus are the ones that are utilized the most frequently in biosurfactant manufacturing. A significant number of currently available publications have demonstrated their efficacy in biosurfactant production and their role in successfully managing phytopathogens [5,117–119] . Varnier et al., [120] concluded that Pseudomonas aeruginosa produced Rhamnolipid biosurfactants that improved grapevine immunity against Botrytis cinerea .…”
Section: Application Of Biosurfactantmentioning
confidence: 99%